HIV/AIDS : oxidative stress and dietary antioxidants - Preedy, Victor R.; Watson, Ronald R. (Ronald Ross) (Academic Press, 2018)
This book examines oxidative stress in HIV/AIDS, focusing on both the pathological process around molecular and cellular metabolism and the complications that can arise due to nutritional imbalance. For virologists, immunologists, physicians, clinical workers, food scientists and nutritionists.